Flipped classroom activities cooperated with graphic organizer technique to enhance grade 11 students’ conceptual understanding of circular and lymphatic systems - Srisa, Supanna; Cojorn, Kanyarat (Journal of Green Learning, 2025)
The purpose of the study was to examine the effectiveness of flipped classroom activities cooperated with graphic organizer technique as principles of a learning lesson plan to develop grade 11 students’ conceptual understanding of circular and lymphatic system. The participants were 40 grade 11 students from a suburban school in northeastern Thailand, participants were sampled by cluster sampling. The instruments included a flipped classroom activities cooperated with graphic organizer technique a learning achievement test, and a conceptual understanding test. Data were analyzed using the effectiveness test and a rubric for conceptual understanding. The results indicated that the flipped classroom activities cooperated with graphic organizer technique effectively improved students’ conceptual understanding of circular and lymphatic system, with most students demonstrating sound understanding of the concept. This study contributes to the field by proving that the flipped classroom activities is beneficial for older students, even within the thai educational context. it also confirmed that flipped classroom activities is particularly effective in teaching complex concepts in sceine education.